Analysis of The Implementation of Environmental Accounting - Fauzia, Annisa; Dunakhir, Samirah; Anwar, Azwar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims: to analyze the application of environmental accounting at PT Pelindo Terminal Petikemas New Makassar. The data collection methods used were interviews and documentation. The types and sources of data obtained were primary and secondary while the analysis method used was the qualitative descriptive analysis method. Based on the research results, it was found that PT Pelindo Terminal Petikemas New Makassar has not implemented comprehensive environmental accounting, because PT Pelindo does not present a separate report regarding environmental management and in the Notes to the Financial Report (CaLK) environmental management costs are not disclosed in detail.